Asuhan Keperawatan pada Lansia dengan Osteoarthritis: Studi Kasus (IJM: Journal of Multidisiplinary, 2025)
This condition significantly impacts the quality of life of older adults, particularly through joint pain, limited mobility, and reduced physical function that interferes with daily activities. This study aims to provide an overview of how effective nursing care is obtained in patients with chronic pain health problems, impaired physical mobility, and risk of falling. In the case of Mrs. S, it was found that complaints of pain in the lower back and legs. So that the client has difficulty walking. The author provides education on increasing knowledge related to osteoarthritis and nonpharmacological pain management by means of warm compresses of ginger water, training Range of Motion (ROM), and education on how to use the correct three-legged stick to Mrs. S. After 10 days of treatment, an evaluation was obtained that there was an increase in knowledge related to osteoarthritis and pain management by means of warm compresses of ginger water on Mrs. S with an increase in knowledge related to osteoarthritis. S with a pain scale before the intervention of 4 NRS and after the intervention to 2 NRS, an increase in knowledge in Mrs. S related to Range of Motion (ROM), an increase in knowledge of fall risk prevention, environmental modification and the correct use of a three-legged cane in Mrs. S. It is recommended to health workers to continue warm ginger water compresses to reduce pain in the elderly, range of motion and prevention of falls in the elderly.